Genome-wide association and Mendelian randomization study of NT-proBNP in patients with acute coronary syndrome - Johansson, Åsa; Katus, Hugo (Human molecular genetics, 2016)
Abstract. N-terminal pro-B-type natriuretic peptide (NT-proBNP) is a strong predictor of mortality in coronary artery disease and is widely employed as a progn
Gesehen am 25.11.2019